Reform of the Calculation of Premium Contributions for State Administrator Participants - Jath, Ar Razaq Subhan; Arvita, Widhy; Isrok, Muhammad; Siregar, Manda Ananda Doly (BPJS Kesehatan, 2024)
This study aims to assess the impact of the reform of the calculation of premium contributions from state administrators collecting based on Presidential Regulation Number 64 of 2020 with Local Government Contribution Reconciliation Application (ARIP), which involves a collaboration with stakeholders, namely the regional government, which is related to increasing the receipt of contributions from regional civil servants in revenue and stakeholder involvement for the sustainability of the National Health Insurance Program. ARIP is an information system that aims to ensure accountability in calculating contributions from regional officials through reconciling contributions between local governments and BPJS Kesehatan. The research used a population of 547 regional governments that used ARIP during 2020-2023. Each sample was analyzed before and after using ARIP quantitatively and descriptively based on receiving contributions from regional civil servants. The hypothesis was tested using paired samples t-test, with significance 0.001< 0.05 and value of t-count = 6.973> t-table = 1.964, then Ha was accepted. Thus, the acceptance of contributions from regional civil servants differs before and after the implementation of ARIP. According to the Cohen classification table, ARIP had a medium impact on accepting the receipt of contributions from regional civil servants, with an effect size of 0.298. Based on the analysis, implementing ARIP increases the receipt of contributions from regional officials, which was 41.303 billion rupiah and increased by 3.234 billion rupiah to 44.537 billion rupiah